2017
DOI: 10.1002/2016ef000410
|View full text |Cite
|
Sign up to set email alerts
|

Arctic ice management

Abstract: As the Earth's climate has changed, Arctic sea ice extent has decreased drastically. It is likely that the late-summer Arctic will be ice-free as soon as the 2030s. This loss of sea ice represents one of the most severe positive feedbacks in the climate system, as sunlight that would otherwise be reflected by sea ice is absorbed by open ocean. It is unlikely that CO 2 levels and mean temperatures can be decreased in time to prevent this loss, so restoring sea ice artificially is an imperative. Here we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
1
30
0
1
Order By: Relevance
“…Others argue that it might be possible to chill just the north, for instance by artificially whitening the Arctic Ocean with light-coloured floating particles to reflect sunlight. A study 9 this year suggested installing wind-powered pumps to bring water to the surface in winter, where it would freeze, forming thicker ice.…”
Section: Global Coolingmentioning
confidence: 99%
“…Others argue that it might be possible to chill just the north, for instance by artificially whitening the Arctic Ocean with light-coloured floating particles to reflect sunlight. A study 9 this year suggested installing wind-powered pumps to bring water to the surface in winter, where it would freeze, forming thicker ice.…”
Section: Global Coolingmentioning
confidence: 99%
“…Several climate engineering approaches that focus on the Arctic sea ice cover and the positive ice‐albedo feedback have been proposed (Cvijanovic et al, ; Desch et al, ; Field et al, ; Mengis et al, ; Seitz, ). The Arctic Ice Management (AIM) strategy put forward in Desch et al (, D17 hereafter), which attracted the attention of the scientific community and the media alike (rated within the top 5% of all research output; Altmetric Attention Score, ), entails the large‐scale employment of wind‐driven pumps that spread seawater on the ice surface in the winter months. The sea ice and the snow that is accumulated over it are materials with low thermal conductivity compared to the ocean water.…”
Section: Introductionmentioning
confidence: 99%
“…Other geoengineering solutions propose to reverse the melting of the Arctic sea ice, by pumping seawater from under the Arctic ice cover to the top of it [12,13]. Figure 1 represents a barge designed to increase the thickness of the Arctic ice cover.…”
Section: Introductionmentioning
confidence: 99%